2019
DOI: 10.2147/ott.s200446
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effects of BCc1 nanoparticle and its mixture with doxorubicin on survival of murine 4T1 tumor model</p>

Abstract: Background: Our previous findings showed that BCc1, a nanoparticle designed based on nanochelating technology, can be considered a new anti-cancer nanoparticle if confirmed by complementary studies. Goal: In the present study, we investigated the effects of the BCc1 nanoparticle alone on some gene expressions influencing the apoptosis pathway, and also the effect of the mixture of BCc1 nanoparticle and doxorubicin on survival. Method: Using an in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…The animal treatment protocol was approved by the Italian Ministry of Health (authorization number 807/2017-PR). When the tumor reached volumes of around 150-200 mm 3 , the animals were treated three times at 1-day intervals (days 0, 2 and 4) intravenously via the tail vein at a dose of 5 mg/kg of doxorubicin (26)(27)(28).…”
Section: Flow Cytometrymentioning
confidence: 99%
“…The animal treatment protocol was approved by the Italian Ministry of Health (authorization number 807/2017-PR). When the tumor reached volumes of around 150-200 mm 3 , the animals were treated three times at 1-day intervals (days 0, 2 and 4) intravenously via the tail vein at a dose of 5 mg/kg of doxorubicin (26)(27)(28).…”
Section: Flow Cytometrymentioning
confidence: 99%
“…This nanomedicine could induce apoptosis and cell arrest in cancer cells as well as their genes expression [19]. In a cancer animal model, it was demonstrated that the mixture of BCc1 nanomedicine and doxorubicin could increase the mean OS of the cancer mice by 48%, where doxorubicin dose was reduced by 50 times [46].…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] In the previous studies, anti-neoplastic effects of BCc1 nanomedicine with iron-chelating property were demonstrated in several experiments. 19,20,47 In the present study, this nanomedicine was tested in animal model of DKD to evaluate its impacts on various biochemical and histopathological parameters of this disease.…”
Section: Discussionmentioning
confidence: 99%